Inflation theory in economics : welfare, velocity, growth and business cycles - Gillman, Max. (London ; New York : Routledge, 2009)
The publication provides an overview of inflation. Issues discussed include, theory of inflation, business cycle, inflation and growth, money supply and welfare.
Includes bibliographical references (p. [377]-394) and index.
lje 30/04/13
Loan
Keywords: Inflation (Finance); Monetary policy